Projeto de máquina de vendas automática de suplementos alimentares - Silva, Caique Walter Ribeiro Harger da (2019)
The fitness market is a huge market on a global lebel with plenty opportunities. This market has over 170 milions clients 200 thousands centers of trainment and an annual income of over 82 billions of reais. Nowdays Brasil is the second in the ranking of centers of traiment and food supplements are present in 54% of the brazillian homes, where 16% are protein supplements and 12% aminoacids. At the same time vending machines represent a great market opportunity when the national market is compared to the international market. The present dissertation proposes the development of a food supplement vending machine to be used in the center of trainment looking forward to bring to the final customers agility and disponibility of food supplements.